The Influence Of Transformational Leadership, Power Distance, And Followership On The Capability Of Making A First Decision In Kostrad - Burhanudin Amin; Hamidah; Kazan Gunawan (Fakultas Ekonomi, Universitas Negeri Jakarta, 2020)
The purpose of the study is to analyze the influences of Transformational Leadership, Power Distance and Followership on the Capability of Officers' Decision Making in Kostrad. The research method used is the survey method which is taken from 293 respondents and associative research explanations using the quantitative research. The writer uses path analysis as the data analysis techniques. The results of the study shows that (1) Transformational Leadership has a direct positive effect in Decision Making Capabilities, (2) Power Distance has a direct positive effect in Decision Making Capabilities, (3) Followership has a direct positive effect in Decision Making Capabilities, 4) Transformational leadership has a direct positive in Followership, (5) Power Distance has a direct positive effect in Followership, (6) Transformational leadership has a direct positive effect in Decision Making Capabilities that has a direct positive effect in Power Distance, (7) Transformational leadership is influential not through the Power Distance mediation variable, (8) Transformational leadership has a positive indirect effect in Decision Making Capabilities through mediation in Followership variables. (9) Power Distance has an indirect positive effect in Decision Making Capabilities through mediation in Followership variables.